Co9S8 nanoparticle-decorated carbon nanofibers as high-performance supercapacitor electrodes. Issue 48 (3rd August 2018) - Zhang, Ning; Wang, Wencong; Teng, Changqing; Wu, Zongxiao; Ye, Ziran; Zhi, Mingjia; Hong, Zhanglian
Abstract : Through electrospinning and the ion-exchange method, Co9 S8 nanoparticle-decorated carbon nanofibers (Co9 S8 /CNF) have been fabricated, and exhibit good supercapacitor performance. Abstract : This work reported Co9 S8 nanoparticle-decorated carbon nanofibers (CNF) as a supercapacitor electrode. By using a mild ion-exchange method, the cobalt oxide-based precursor nanoparticles were transformed to Co9 S8 nanoparticles in a microwave hydrothermal process, and these nanoparticles were decorated onto a carbon nanofiber backbone. The composition of the nanofibers can be readily tuned by varying the Co acetate content in the precursor. The porous carbon nanofibers offered a fast electron transfer pathway while the well dispersed Co9 S8 nanoparticles acted as the redox center for energy storage. As a result, high specific capacitance of 718 F g −1 at 1 A g −1 can be achieved with optimized Co9 S8 loading. The assembled asymmetric supercapacitor with Co9 S8 /CNF as the cathode showed a high energy density of 23.8 W h kg −1 at a power density of 0.75 kW kg −1 and good cycling stability (16.9% loss over 10 000 cycles).